PENGARUH LATIHAN BOX JUMP TERHADAP POWER OTOT TUNGKAI PADA TIM BOLAVOLI PUTRA SATPOL PROVINSI RIAU - Nasution, Muhammad Ali; Slamet, Slamet; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: From the observations of researchers in the field, the Satpol players of Riau Province. Researchers observed that in training sessions and in matches, there are still many shortcomings of Satpol players in Riau Province. One of them is like the leg muscles when jumping during a smash or block. The purpose of this study was to determine the effect of box jump training on leg muscle power in the men's volleyball team Satpol Riau Province. The population in this study were 12 men's volleyball team Satpol Riau Province. The sampling technique used total sampling, so that the sample in this study amounted to 12 people. To measure the power of the leg muscles using a vertical jump. The data obtained were analyzed using the t-test. Based on data analysis and discussion, it can be concluded that there is an effect of Box jump training on leg muscle power in the Riau Provincial Satpol Men's team, proven by the results of tcount 4.723> t table 1.796 at α = 0.05. This proves that by doing Box jump exercise, leg muscle power can get better results. Key Words: Box jump, Leg Muscle Power